Analisis Kepuasan Konsumen Jeruk Siam Gunuang Omeh - Safitri, Dena; Silfia, Silfia; Arnayulis, Arnayulis (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Gunuang Omeh Siamese orange or Jesigo is a siamese citrus variety that is cultivated in Gunuang Omeh District, Lima Puluh Kota Regency, West Sumatra. Gunuang Omeh Siamese oranges are the leading agricultural commodity in Fifty Cities Regency. This orange is widely liked by the public but its promotion is still not widespread and it is still not distributed in good packaging. Therefore, it is necessary to see how consumer satisfaction with the Siam Gunuang Omeh product is based on the existing attributes. Based on these problems, research was conducted to see how consumer satisfaction with jesigo products was seen from the attributes. The analysis carried out was quantitative descriptive analysis using the Importance Performance Analysis (IPA) method to identify the position of important attributes or priorities for jesigo consumers and Customer Satisfaction Index (CSI) analysis technique is used to analyze the level of consumer satisfaction with the quality of jesigo's products. The results of this study indicate that in the Importance Performance Analysis (IPA) the position of the Gunuang Omeh Siamese Citrus attribute is spread to four quadrants where in quadrant A or the main priority quadrant there is only one attribute, namely the safe packaging attribute for the Gunuang Omeh Siam Orange product, for quadrant B. or the maintain achievement quadrant there are several attributes, namely taste, price and product cleanliness, sales locations are easy to find, for the C quadrant or low priority quadrant there are attractive packaging and promotional attributes, and for the D quadrant or excessive quadrant there are size and storability attributes. Furthermore, there is one attribute that lies between the two quadrants, namely the Jesigo aroma attribute which is located right on the dividing line between the maintain achievement quadrant and the excessive quadrant. The value of the Customer Satisfaction Index shows that the consumers of the Jeruk Siam Gunuang Omeh or Jesigo products feel "Satisfied" with the attributes of the Jesigo products offered with a satisfaction value of 79.92%.